2015
DOI: 10.1080/10407782.2015.1031597
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the FTnFinite Volume Method for Transient Radiative Transfer in Anisotropically Scattering Medium

Abstract: In this paper, we formulated, applied, and tested the FTn Finite Volume Method (FTn FVM) for transient radiative transfer in three-dimensional absorbing, emitting, and anisotropically scattering medium. Both the STEP and the Curved-Line Advection Method (CLAM) are introduced for spatial discretization of the transient radiative transfer equation. The results show that FTn FVM reduces largely the ray effects and it is more accurate than the standard FVM. Also, using both STEP and CLAM schemes, FTn FVM has small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The Monte Carlo [5][6][7][8][9], the integral equation (IE) formulation [10][11][12], and the discrete ordinates [13][14][15] methods have been developed to study the unsteady radiative heat transfer. The finite volume method (FVM) has been also developed and used [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Several researchers have demonstrated that he FVM has a respectable compromise between precision, flexibility, and moderate computational conditions [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Monte Carlo [5][6][7][8][9], the integral equation (IE) formulation [10][11][12], and the discrete ordinates [13][14][15] methods have been developed to study the unsteady radiative heat transfer. The finite volume method (FVM) has been also developed and used [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Several researchers have demonstrated that he FVM has a respectable compromise between precision, flexibility, and moderate computational conditions [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The finite volume method (FVM) has been also developed and used [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Several researchers have demonstrated that he FVM has a respectable compromise between precision, flexibility, and moderate computational conditions [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. It is also known by its compatibility with other methods applied in computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors achieved an acceptable compromise between the FVM results by applying the normalization technique, and the two different methods by little effect on computational efficiency. Guedri et al [23] formulated and applied the FTn Finite Volume Method (FTn FVM) for transient radiation in a 3-D absorbing, emitting, and anisotropically scattering medium. The outcomes illustrated that FTn FVM decreases mostly the ray impacts and its accuracy is higher Energies 2019, 12, 3986 3 of 22 than the standard FVM.…”
Section: Introductionmentioning
confidence: 99%
“…22 Accordingly, in the present work, high-order spatial resolution schemes of the FVM, based on the NVD formulation, are used to solve the RTE in 2D/3D rectangular enclosures containing transparent, emitting-absorbing, emitting-absorbing-scattering, or nonhomogeneous media. To reduce the angular discretization errors, a nonuniform angular discretization, namely, the FTn, [23][24][25][26][27][28][29] is implemented. The results of the STEP and NVD schemes are compared with those obtained using analytical and more accurate methods.…”
Section: Introductionmentioning
confidence: 99%